The Impact of Content Marketing and Brand Experience in Achieving Customer Response: An Exploratory Study of the Opinions of a Sample of Customers of the Southern Cement Company - Ordinary Porttland Cement Product - Ahmed Kadem Abed AL Aboudy; Kareem Hassan Mjali; Ali Thamer Abdul Ameer (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research explores the combined effects of content marketing and brand experience on customer response, a relationship that has not been extensively studied in previous research. The study highlights the significance of customer service as a key determinant of business success, emphasizing that when customers feel valued and receive prompt responses from a company, their satisfaction, loyalty, and willingness to engage with the brand increase. The research was conducted on a sample of customers from the General Company for Southern Cement, specifically the Kufa Cement Factory. The study focused on Ordinary Portland Cement and sulfate-resistant cement. A total of 85 questionnaire forms were distributed, with 80 valid responses collected for statistical analysis.The findings indicate that both content marketing and brand experience play a crucial role in enhancing customer communication and service quality. Effective content marketing strategies contribute to better training for customer support teams, ensuring a more responsive and engaging interaction with customers. Furthermore, improving communication channels and response speed positively impacts customer satisfaction. By adopting content marketing strategies and leveraging brand experience, businesses can enhance customer engagement, strengthen relationships, and ultimately achieve their organizational goals.The research recommends integrating content marketing into business operations to build long-term customer relationships and improve brand reputation. Additionally, companies should establish a dedicated internal department for marketing, ensuring that content marketing efforts are credible, relevant, and engaging. By creating meaningful and interactive content, businesses can attract and retain customers, fostering brand loyalty and trust over time.